1991
DOI: 10.1002/joc.3370110408
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal air and road surface temperature variations in complex terrain

Abstract: This paper is part of an ongoing project dealing with the modelling of local climate for predicting temperature variations and risks of road slipperiness under various synoptic conditions. Temperature recordings from mobile measurements taken along road stretches have been analysed to determine the influence of valleys on the variation in air and road surface temperatures. During clear, calm nights, the variation in air temperature between valley bottoms and surrounding areas can be related to geometric proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…These included: (i) Splines [35], (ii) Nearest Neighborhood [36], (iii) Polynomial [37], (iv) Kriging [38], (v) Inverse Distance Weighted (IDW), (vi) Triangular Integrated Network (TIN) [39], and (vii) Radial Basis Function (RBF) [40]. Based on our visual and statistical assessment of the resulting surfaces, IDW produced the smoothest appearing surface based on locally varying values; which is consistent with the conceptual models of locally explicit, but regionally continuous microclimatic variability [29,30]. Therefore, we have used IDW interpolation for the remainder of this analysis.…”
Section: Spatial Interpolation Of Road Temperature Variationssupporting
confidence: 70%
See 1 more Smart Citation
“…These included: (i) Splines [35], (ii) Nearest Neighborhood [36], (iii) Polynomial [37], (iv) Kriging [38], (v) Inverse Distance Weighted (IDW), (vi) Triangular Integrated Network (TIN) [39], and (vii) Radial Basis Function (RBF) [40]. Based on our visual and statistical assessment of the resulting surfaces, IDW produced the smoothest appearing surface based on locally varying values; which is consistent with the conceptual models of locally explicit, but regionally continuous microclimatic variability [29,30]. Therefore, we have used IDW interpolation for the remainder of this analysis.…”
Section: Spatial Interpolation Of Road Temperature Variationssupporting
confidence: 70%
“…This is because: (i) roads are relatively well distributed over modern urban environments, (ii) their primary construction materials are generally the same for different major road types within a given city, thus providing consistent thermal properties [28], and (iii) previous research has revealed a strong correlation between night-time air temperature and road surface temperature [29,30], from which we assume that the road temperature can be used to model urban microclimatic variability in terms of energy flux.…”
Section: Pseudo Invariant Features and Mode Road Temperaturementioning
confidence: 99%
“…Gustavsson, 1991, Gustavsson et al, 1998). The noticeable increase in scatter in Figure 4(b) is probably due to cold air pooling in stable night time conditions, which is more directly related to local topography than elevation above sea level (Bogren and Gustavsson, 1991;Gustavsson, 1999;Bogren et al, 2000). A more detailed study of observed night time γ as a function of cloud cover and wind was performed for the Devon stations by compiling γ values as implied by the slopes of plots such as Figures 4(a) and (b) constructed for nights in winter 2006-2007.…”
Section: Behaviour Of the Environmental Lapse Ratementioning
confidence: 99%
“…Bogren & Gustavsson (1991) have shown in some detail how topography affects the spatial variation of air and road temperature in Sweden. With the present study, the situation on 16 February presented a problem when face-based observations of cloud.…”
Section: Resultsmentioning
confidence: 99%